The Influence of Transformational Leadership Style, Work Motivation, and Work Discipline on Affective Commitment (A Case Study of Employees at STIE APRIN Palembang) - Supriyatno, Supriyatno (Jurnal Ar Ro'is Mandalika (Armada), 2024)
The purpose of this study is to identify and analyze the influence of each variable—both individually and simultaneously—on affective commitment among employees at STIE APRIN. The research sample consisted of 52 respondents who are employees of STIE APRIN, selected using a saturated sampling technique. A quantitative approach was applied, based on positivist philosophy and aimed at collecting numerical data from the field. The data were analyzed using multiple linear regression analysis. The t-test results showed that: (1) transformational leadership style has a significant effect on affective commitment (p = 0.003); (2) work motivation has a significant effect on affective commitment (p = 0.013); (3) work discipline does not have a significant effect on affective commitment (p = 0.058). Meanwhile, the coefficient of determination (R²) test showed that simultaneously, the three variables explain 47.8% of the variation in affective commitment, while the remaining percentage is influenced by other variables not included in this study.